Awarding Support Becomes a Dominant Factor in the Election of Family Planning in the Long-Term Contraception Method in Kampung KB - Ningsih, Dewi Ayu; Firdawati, Firdawati; Satria, Pom Harry (Universitas Aisyah Pringsewu, 2019)
Indonesia’s Maternal Mortality Rate (MMR) is currently in the high category. One effort to reduce MMR is through family planning program. The family planning program contributes in reducing 32% all of maternal mortality by increasing the coverage of LARC users whose achievements are currently only 17.45%. One of the biggest influences on the escalation of LARC users is psychosocial support from the environment. The objective of this study analyzed the relationship between emotion, informational, instrumental, and appraisal supports from the environment with the LARC use in the Kampung KB. The research used an observational analytic design with a cross-sectional approach to 100 respondents that acceptor KB. Statistic analysis used the chi-square and logistic regression. The results of this study showed that the emotional, instrumental and appraisal support were associated with LARC use, based on the p values of 0.028, 0.019 and 0,001, respectively. Appraisal support became the dominant factor in choosing LARC in Kampung KB with an odds ratio (OR) 5,000. It meant that a woman who got appraisal support from the environment have 5,000 times higher to have an opportunity to use LARC than the woman who did not get the appraisal support.ABSTRAKAngka Kematian Ibu (AKI) Indonesia saat ini masih dalam kategori tinggi. Salah satu strategi menurunkan AKI adalah program KB. Program KB berkontribusi dalam menurunkan 32% dari seluruh kematian ibu dengan cara meningkatkan cakupan pengguna KB MKJP yang saat ini capaiannya hanya 17,45%. Peningkatan pengguna KB MKJP salah satunya dipengaruhi oleh dukungan psikososial dari lingkungan. Penelitian ini bertujuan menganalisis hubungan antara dukungan emosional, informasional, instrumental, dan penghargaan dari lingkungan dengan penggunaan KB MKJP di Kampung KB. Penelitian ini menggunakan desain analitik observasional dengan pendekatan cros-secsional terhadap 100 responden akseptor KB. Analisis statstik yang digunakan adalah uji chi-square dan regresi logistik. Hasil penelitian menunjukkan bahwa dukungan emosional, instrumental dan penghargaan berhubungan dengan penggunaan KB MKJP di Kampung KB, dengan masing-masing nilai p yaitu 0,028, 0,019, dan 0,001. Sementara, dukungan informasional tidak berhubungan dengan nilai p lebih dari 0,05. Dukungan penghargaan menjadi faktor dominan dengan nilai ood rasio (OR) sebesar 5,000. Seseorang yang memperoleh dukungan penghargaan dari lingkungan akan 5,000 kali berpeluang memilih menggunakan KB MKJP dibanding dengan yang tidak memperoleh dukungan penghargaan.